Peripheral nerve high‐resolution ultrasound in diabetes. Issue 2 (10th November 2016) - Breiner, Ari; Qrimli, Mohammad; Ebadi, Hamid; Alabdali, Majed; Lovblom, Leif E.; Abraham, Alon; Albulahi, Hana; Perkins, Bruce A.; Bril, Vera
ABSTRACT: Introduction: High‐resolution ultrasound (HRU) is used in the diagnosis of peripheral neuropathies. There are conflicting data regarding HRU findings in patients with diabetic sensorimotor polyneuropathy (DSP). Our purpose in this study was to measure nerve cross‐sectional areas (CSAs) in patients with diabetes, with and without DSP. Methods : We performed a prospective peripheral nerve HRU study of 100 diabetic subjects, assessed the CSA at predefined sites, and compared the results with those of 100 normal subjects. We evaluated the use of individual CSA values and various summary scores for diagnosis of DSP. Results : Diabetic subjects had higher CSA values than healthy volunteers, and those with DSP had higher CSA values. Three or more enlarged CSA sites predicted DSP with 64% sensitivity and 77% specificity. Conclusions : Peripheral nerves are enlarged diffusely in diabetic patients, including sites not susceptible to bony compression. The number of enlarged CSA values can help predict the presence of DSP. Muscle Nerve, 2016 Muscle Nerve 55 : 171–178, 2017